2014
DOI: 10.1371/journal.ppat.1004323
|View full text |Cite
|
Sign up to set email alerts
|

On the Front Line: Quantitative Virus Dynamics in Honeybee (Apis mellifera L.) Colonies along a New Expansion Front of the Parasite Varroa destructor

Abstract: Over the past fifty years, annual honeybee (Apis mellifera) colony losses have been steadily increasing worldwide. These losses have occurred in parallel with the global spread of the honeybee parasite Varroa destructor. Indeed, Varroa mite infestations are considered to be a key explanatory factor for the widespread increase in annual honeybee colony mortality. The host-parasite relationship between honeybees and Varroa is complicated by the mite's close association with a range of honeybee viral pathogens. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
255
3
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(273 citation statements)
references
References 75 publications
11
255
3
4
Order By: Relevance
“…Varroa levels were significantly elevated in bees positive for both ABPV (Figure 7) and DWV (Figure 8), highlighting the role of Varroa as viral vectors (Ball and Allen 1988;Bowen-Walker et al 1999;Mondet et al 2014). ABPV has long been associated with increased honey bee mortality in mite-infested colonies (Ball and Allen 1988).…”
Section: Discussionmentioning
confidence: 98%
“…Varroa levels were significantly elevated in bees positive for both ABPV (Figure 7) and DWV (Figure 8), highlighting the role of Varroa as viral vectors (Ball and Allen 1988;Bowen-Walker et al 1999;Mondet et al 2014). ABPV has long been associated with increased honey bee mortality in mite-infested colonies (Ball and Allen 1988).…”
Section: Discussionmentioning
confidence: 98%
“…There are concerns about the decline in populations of managed honey bees observed since 2006 (3). Often, this decrease in honey bee numbers is attributed to infection with several species of viruses (4) and the wide-spread ectoparasitic mite Varroa destructor (5), which can double as a viral vector. Multiple studies have shown that deformed wing virus (DWV), particularly when associated with high levels of V. destructor infestation, is linked to overwintering losses of colonies and "colony collapse disorder," where the number of adults bees in a particular hive plummets dramatically as a consequence of unexplained factors (3,(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…In particular, these models highlight the build-up of phenotypic variation between the front and the rear of a spreading epidemic. In accord with these theoretical results, recent field studies report the existence of patterns of phenotypic differentiation between pathogens sampled at the front or at the epicentre of epidemics [19,[23][24][25].…”
Section: Introductionmentioning
confidence: 60%